NON-FINANCIAL FACTORS AFFECTING FINANCIAL PERFORMANCE IN INDONESIAN NCSR AWARD RECIPIENT COMPANIES - Alfonsa Dian Sumarna; Widya Putri Muzakir (Berkala Akuntansi dan Keuangan Indonesia, 2022)
Non financial factors that affect financial performance have many different findings that cause research gaps. This study analyzes the influence of Corporate Social Responsibility (CSR) in more detail instruments by proxying it into variabel Employee Relations, Community, Product, Environment and the Good Corporate Governance (GCG) are proxied into Number of Independent Board of Commissioners, Institusional Ownership, Audit Quality on Return on Assets as the financial performance from companies that receive awards from the National Center of Sustainability Reporting Indonesia. The research uses partial test and simultaneous test using SPSS. Because the impact of CSR and GCG is not directly related to performance, the finance performance variable is calculated one year after the company implements CSR and GCG. The result showed that the implementation of CSR and GCG has a significant effect simultaneously on financial performance. Partially which has a significant effect is CSR with the proxy of community and environment variable. Non-financial factors (CSR and GCG) affect 21,4% of the company’s financial performance.